Piriformospora indica and new generation fungicides for the management of Anthracnose incited by Colletotrichum gloeosporioides (Penz.) Sacc. in vegetable Cowpea - Amrutha, P; Joy, M (Guide) (Vellayani Department of Plant Pathology, College of Agriculture, 2025)
An investigation on (3z(BPiriformospora indica and new generation fungicides for management of anthracnose incited by Colletotrichum gloeosporioides (Penz.) Sacc. in vegetable cowpea(3y (Bwas carried out at Department of Plant Pathology, College of Agriculture, Vellayani during 2017-2022. The objective was to study the host range of C. gloeosporioides causing anthracnose disease (leaf blight, girdling and blight of stem and fruit rot) of vegetable cowpea and to evaluate the efficacy of fungal root endophyte, P. indica and new generation fungicides for its management. The typical symptoms of vegetable cowpea anthracnose viz., dark brown circular to irregular spots on the leaves, midrib, stems, branches and pods were observed during the survey conducted in ten locations representing five agro-climatic zones (ACZ) of Kerala. The disease severity as percentage disease index (PDI) and disease incidence (DI) recorded from different zones showed a highest from farmers field, Kottarakkara (PDI-73.50 and DI-51%) in southern zone and lowest from RARS, Pattambi (PDI-23.56 and DI-16%) in central zone. The pathogen was isolated on potato dextrose agar (PDA) medium and ten isolates of C. gloeosporioides were obtained. The isolates were named as Cg1 to Cg10. The isolates produced white to grey coloured colonies with regular margin and the conidia appeared cylindrical or straight with round or obtuse apex. Cg1 isolate recorded maximum radial mycelial growth of 9 cm within 7 days of inoculation compared to other isolates. Screening of the most virulent isolate among the ten isolates was done by spraying the spore suspension of the pathogen (106 to 107 cfu ml-1) on to vegetable cowpea var. Vellayani Jyothika and Cg1 produced largest lesion size of 6.56 cm and PDI of 85.94 (most virulent) followed by Cg4 (lesion size-4.56 cm, PDI-65.83); whereas Cg7 was the least virulent isolate (lesion size-0.46 cm, PDI-26.03) at 10 day after inoculation (DAI). Screening of nine vegetable hosts viz., brinjal, cucumber, pumpkin, chilli, tomato, amaranth, winged bean, bean and bush cowpea against Cg1 by detached leaf assay using mycelial bits revealed brinjal as the most susceptible host with a lesion size of 5.9 cm, followed by pumpkin and cucumber (lesion size - 4.9 cm) and the least susceptible host as bush cowpea (1.5 cm) at 7 DAI. Similarly, seven KAU and one IIHR cowpea varieties screened against Cg1 indicated Arka Garima (PDI-76.5) followed by Vellayani Jyothika (PDI-66.06) as the most susceptible varieties and Anaswara (PDI-11.9) as tolerant variety at 10 DAI. Poison food technique and spore germination assay were carried out with triazoles, strobilurins and their combination fungicides at 10, 50, 100 and 250 ppm against Cg1. Trifloxy-strobin 25 % + tebuconazole 18.3 % SC followed by azoxystrobin 11 % + tebuconazole 18.3 % SC and difenoconazole 25% EC at 250 ppm recorded highest inhibition of mycelial growth higher than 88 per cent; whereas, strobilurin fungicide pencycuron 22.9 % SC recorded least inhibition of 18.89 per cent. Hexaconazole 5EC and difenoconazole 25% EC (250 ppm) drastically reduced the spore germination by 97.67 per cent. Compatibility study of P. indica with systemic insecticides and fungicides showed that thiamethoxam 25% WG and flubendiamide 39.35% SC at 250 ppm as the most compatible (62.22% and 61.11%) and chlorpyriphos 20 EC as the least compatible insecticides at 7th DAI; whereas trifloxystrobin 50 WG and trifloxystrobin 25 % + tebuconazole 18.3 % SC at 350 ppm as the most compatible (74.44% and 68.89%) and hexaconazole 5EC and difenoconazole 25% EC (0%) as the least compatible systemic fungicides on 10 DAI. Colonization of P. indica in vegetable cowpea var. Vellayani Jyothika was carried out using dried FYM - coir pith - gram flour amended medium. The roots were examined for colonization at regular intervals. The endophyte started colonising the roots and observed young chlamydospores at 5 days after germination (DAG) and the colonization was high in roots at 15 DAG with mature chlamydospores arranged in chains inside the cortical cells of roots. In both in vitro and in vivo experiments, P. indica-colonized vegetable cowpea plants reduced severity of anthracnose to 77.17 and 62.41 per cent compared to non-colonized plants on 20 and 35 DAI respectively. The beneficial fungal endophyte colonization also improved the shoot and root biomass of the plants at 20 and 35 DAI respectively. P. indica-colonization followed by spraying of systemic fungicides viz., trifloxystrobin 25 % + tebuconazole 18.3 % SC and carbendazim 50 WP drastically reduced the disease severity to 64.44 and 59.1 per cent respectively at 50 day after transplanting (DAT). P. indica-colonization also reduced the residues of trifloxystrobin 25 % + tebuconazole 18.3 % SC (17%) and carbendazim 50WP (16.6%) in the crop. Field trials were laid out with P. indica-colonized and P. indica-non-colonized vegetable cowpea var. Vellayani Jyothika at Instructional Farm, College of Agriculture, Vellayani in two seasons [rabi (2019) and summer (2020)] on natural incidence of anthracnose. P. indica-colonized plants recorded a drastic reduction in severity of the disease (63.21 and 64.47); in addition to cercospora leaf spot (54.81 and 58.7) and Blackeye cowpea mosaic virus (54.16 and 56) in rabi and summer seasons. Enhanced shoot weight (35 and 35.73%), root weight (24 and 25.55%), number of root nodules (22.72 and 23.25%), number of pods (18.96 and 22.02%), length of pods (13.5 and 12.81%), number of flowers (20 and 25.8%), seeds per pod (21.73%), average weight per pod (16.12 and 19.04%) and average yield per plant (35.34 and 36.91%) were observed in P. indica-colonized plants at 90 DAT in rabi and summer. Biochemical analysis of defence enzymes at 0, 12, 24 and 72 hours after inoculation (HAI) showed a significant increase in the activities of chitinase (21.11%) and gb(B, 1-3 glucanase (11.89%) and also total phenolics (4.63%) in plants colonized with P. indica and challenge inoculated with C. gloeosporioides compared to the non colonized plants inoculated with the pathogen at 72 HAI. P. indica-colonization also reduced the accumulation of reactive oxygen species (ROS) which was visualized as dark blue stain of formazan compound; and hydrogen peroxide visualized as dark brown stain; as analysed by nitroblue tetrazolium (NBT) and 3, 3$1 (B-diaminobenzidine (DAB) staining respectively. Molecular analysis of genes involved in P. indica-mediated tolerance against anthracnose of vegetable cowpea indicated a downregulation of ROS marker genes (Zinc finger transcription factor (ZAT10), Redox responsive transcription factor (RRTF1), Heat shock protein (HSPRO), O-methyl transferases (OMT) and MYB51) at 12, 24 and 72 h; and upregulation of antioxidant genes (ascorbate peroxidase (APX), monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR) and glutathione reductase (GR)) at 24 and 72 h by bringing down the programmed cell death. P. indica-colonization also upregulated the expression of abscisic acid signalling genes (Abscisic acid aldehyde oxidase (AAO3-2), Abscisic acid insensitive (ABI 11) and 1-Aminocyclopropane-1-carboxylic acid (ACCS2)) and ethylene signalling genes (ethylene response 1 (ETR 1), ethylene insensitive (EIN1) and ethylene response factor (ERF1)) which are involved in defence responses. Therefore, the present study reveals that brinjal, pumpkin and cucumber are the most susceptible host of C. gloeosporioides causing anthracnose in vegetable cowpea; which implies the restriction of cultivation of the above vegetable crops near to vegetable cowpea. Combination fungicides of triazoles and strobilurins, and triazole fungicides were most effective against C. gloeosporioides. The beneficial fungal endophyte, P. indica was compatible with most of the systemic insecticides and fungicides (except chlorpyriphos and triazoles) used in vegetable cultivation and also reduced their residues in the crop. P. indica-colonization enhanced tolerance against anthracnose, the most important foliar fungal disease, in addition to other fungal and viral diseases with increased growth and yield in vegetable cowpea.s
Ph.D
Keywords: Plant Pathology; Piriformospora indica; Fungicides; Anthracnose incited; Colletotrichum gloeosporioides (Penz.) Sacc; Vegetable Cowpea